Impact of COVID-19 pandemic on glycaemic and blood pressure control among patients with type 2 diabetes in primary care in Hong Kong - Chung Ming Wong; Kit Ping Loretta Lai; Man Hei Matthew Luk; Pang Fai Chan (BMC Primary Care)
Abstract Objectives To evaluate the impact of social distancing measures due to COVID-19 pandemic on glycemic and blood pressure control in primary care in Hong Kong. Methods This was a retrospective cross-sectional study. Diabetic patients with regular follow-up in 8 public primary care clinics in Hong Kong within the study period were recruited. The outcomes were to detect any difference of HbA1c levels and BP between pre-pandemic group (2019 group) and the 1-year post-pandemic group (2020 group) in all patients and in sub-group analysis of different age groups, sex, body mass index, presence of diabetic complications and different diabetic treatment. Results There was no statistically significant change in HbA1c level between 2020 and 2019 groups which was 0.019% (95% confidence interval [CI] -0.057% to 0.094%, p = 0.632). There was also no statistically significant change in both systolic and diastolic BP between 2020 and 2019 groups which were -0.143 mmHg (95%CI -1.005 mmHg to 0.719 mmHg, p = 0.745) and 0.148 mmHg (95%CI -0.422 mmHg to 0.718 mmHg, p = 0.611). Subgroup analysis showed that female gender had statistically significant improvement in glycaemic control (HbA1c 6.92% in 2020 group versus HbA1c 7.03% in 2019 group, p = 0.021). Patients with diabetic retinopathy had statistically significant lower diastolic BP (diastolic BP 73 mmHg in 2020 group versus diastolic BP 75 mmHg in 2019 group with p = 0.011). Conclusions Despite the implementation of various social distancing measures resulting in significant change in lifestyle, COVID-19 pandemic did not worsen glycaemic and blood pressure control in T2DM patients. In fact, slight improvement in glycaemic control among female patients was found. Trial registration Not applicable.